Quanto vale o show? O papel da profissionalização e do talento no rendimento do trabalho em atividades culturais no Brasil - Souza, Marizélia Ribeiro de (2018)
This paper aims to analyze the role of professionalization and the job market talent in culture in Brazil. Therefore, the data is obtained from 2010 Census and the selected courses are those that apply specific skills test, that composes the list of the upper level courses in the Census. These tests are used as a proxy to the talent of the cultural field workers. When verifying the probability determinants that a worker put its labor force to the cultural activities, in exclusive or partial time, or other productive activities, it is observed that having a specific degree on the cultural department tends to increase their incomes, especially to those who work entirely with artistic activities. In addition to the specific training, there are other factors that cannot be observed which influence the insertion and improves the income of the workers in the culture segment, such as the talent. In this paper, it is used an Oaxaca analysis (1973), with the aim to measure this variable. Therefore, the graduation courses in the culture field that require specific skills test are used as proxy.